Indeks triglicerida-glukoze kao biohemijski prediktor hipertenzije kod pacijenata sa dijabetesom tipa 2 i predijabetesom: dokazi iz baze podataka NHANES: TyG Index and Hypertension in Diabetes/Prediabetes - Dai, Tianyu; Wang, Fangze; Deng, Hanqing; Li, Muyuan; Zhang, Jihu; Wang, Jian (Journal of Medical Biochemistry, 2025)
Background: The triglyceride-glucose (TyG) index, derived from fasting triglyceride and glucose levels, has emerged as a reliable biochemical marker of insulin resistance. However, its relationship with hypertension (HTN) in diabetic and prediabetic populations remains insufficiently studied. Methods: Using data from 2,440 adults in the U.S. National Health and Nutrition Examination Survey (NHANES, 2011–2018), we investigated the association between the TyG index and HTN. Biochemical assays included enzymatic measurement of serum triglycerides (Beckman Coulter DxC800) and plasma glucose (hexokinase-based methods on Roche Cobas systems), from which the TyG index and related indices (TyG-BMI, TyG-WC, TyG-WHtR) were calculated. Logistic regression models adjusted for demographic, anthropometric, and biochemical covariates were used to estimate odds ratios (OR) for HTN risk. Results: Participants with HTN exhibited significantly higher TyG index levels compared with non-hypertensives (8.44 vs. 8.38, P<0.01). In fully adjusted models, each unit increase in TyG was associated with a 31% higher risk of HTN (OR=1.31, 95% CI: 1.02–1.69). Stratified analyses revealed significant associations among Mexican Americans and individuals without prior cardiovascular or hepatic disease. TyG-WC and TyG-WHtR indices also correlated positively with HTN risk, whereas TyG-BMI did not. Conclusion: Elevated TyG index and related biochemical indices are independently associated with increased HTN risk among individuals with diabetes or prediabetes. As a simple and reproducible biochemical parameter, the TyG index may serve as a valuable tool in laboratory medicine for early HTN risk identification and prevention strategies.